Complexity of Human Antibody Response to Dengue Virus: Implication for Vaccine Development - Tsai, Wen-Yang; Lin, Hong-En; Wang, Wei-Kung (Frontiers in Microbiology, 2017)
The four serotypes of dengue virus (DENV) are the leading cause of arboviral diseases in humans. Decades of efforts have made remarkable progress in dengue vaccine development. Despite the first dengue vaccine (dengvaxia from Sanofi Pasteur), a live-attenuated tetravalent chimeric yellow fever-dengue vaccine, has been licensed by several countries since 2016, its overall moderate efficacy (56.5−60.8%) in the presence of neutralizing antibodies during the Phase 2b and 3 trials, lower efficacy among dengue naïve compared with dengue experienced individuals, and increased risk of hospitalization among young children during the follow-up highlight the need for a better understanding of humoral responses after natural DENV infection. Recent studies of more than 300 human monoclonal antibodies (mAbs) against DENV have led to the discovery of several novel epitopes on the envelope protein recognized by potent neutralizing mAbs. This information together with in-depth studies on polyclonal sera and B-cells following natural DENV infection has tremendous implications for better immunogen design for a safe and effective dengue vaccine. This review outlines the progress in our understanding of mouse mAbs, human mAbs and polyclonal sera against DENV envelope and precursor membrane proteins, two surface proteins involved in vaccine development, following natural infection; analyses of these discoveries have provided valuable insight into new strategies involving molecular technology to induce more potent neutralizing antibodies and less enhancing antibodies for next-generation dengue vaccine development.